THE ROLE OF SLC26A4 MUTATIONS IN PENDRED SYNDROME: A GENETIC APPROACH TO HEARING AND THYROID DISORDERS (The Research of Medical Science Review, 2024)
Pendred syndrome is a genetic disorder characterized by sensorineural hearing loss and goiter, which can lead to hypothyroidism. This review article aims to unravel the genetic puzzle behind this syndrome. Pendred syndrome is one of the well-known syndromic forms of hereditary hearing loss, representing 30% of cases associated with health issues affecting various systems in the body. The syndrome is caused by malfunction in the pendrin protein, which is responsible for ion transport in the thyroid, kidney, and inner ear. The SLC26A4 gene encodes pendrin, and mutations in this gene have been identified as the root cause of Pendred syndrome. Clinical manifestations include progressive and fluctuating hearing loss, inner ear abnormalities such as enlarged vestibular aqueduct and Mondini dysplasia, and goiter. Understanding the genetic basis of Pendred syndrome is crucial for accurate diagnosis and tailored treatment plans.